2015
DOI: 10.7567/jjap.54.10nb07
|View full text |Cite
|
Sign up to set email alerts
|

Preparation of titanium metal/barium titanate composites with boundary layer structure by hydrothermal method and their dielectric properties

Abstract: To develop metal/insulator composite capacitors with a high effective dielectric constant, we focus on the microstructure of boundary layer (BL) capacitors. Titanium metal/barium titanate (Ti/BT) composites consisting of Ti metal grains and BT boundary nanolayers were successfully prepared from pressed Ti-BT core-shell particle compacts by a hydrothermal method below 230 °C. In this hydrothermal method, BT polycrystalline shell layers connected to each other by crystal growth via a dissolution and reprecipitat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2016
2016
2018
2018

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 32 publications
0
3
0
Order By: Relevance
“…In a previous study, we reported on a hydrothermal process for preparation of the titanium metal/ barium titanate (Ti/BT) composite materials with BL structures and their dielectric properties. 9) In this hydrothermal process, the TiBT coreshell particles were connected to each other by utilizing dissolution and reprecipitation of the BT shell layers in the basic aqueous solutions for construction of the BL structure, because the microstructure of BL capacitors can be considered to comprise an assembly of conductor-insulator coreshell components. While these Ti/BT composite materials with BL structures exhibited a highly effective dielectric constant of over 5000, their dielectric breakdown strength was less than 0.5 kV·cm ¹1 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In a previous study, we reported on a hydrothermal process for preparation of the titanium metal/ barium titanate (Ti/BT) composite materials with BL structures and their dielectric properties. 9) In this hydrothermal process, the TiBT coreshell particles were connected to each other by utilizing dissolution and reprecipitation of the BT shell layers in the basic aqueous solutions for construction of the BL structure, because the microstructure of BL capacitors can be considered to comprise an assembly of conductor-insulator coreshell components. While these Ti/BT composite materials with BL structures exhibited a highly effective dielectric constant of over 5000, their dielectric breakdown strength was less than 0.5 kV·cm ¹1 .…”
Section: Introductionmentioning
confidence: 99%
“…While these Ti/BT composite materials with BL structures exhibited a highly effective dielectric constant of over 5000, their dielectric breakdown strength was less than 0.5 kV·cm ¹1 . 9) The low dielectric breakdown strength of Ti/BT composite materials may be attributed to their polycrystalline BT shell layers, which can provide current leakage paths at the grain boundary of BT. In this study, we tried to improve the dielectric breakdown strength by introducing epitaxial interfaces between the conductor core and insulator shell layers to prevent current leakage.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, BaTiO 3 and related ferroelectric materials have attracted renewed interest from a scientific and technological viewpoint. [1][2][3][4][5][6][7][8][9][10][11][12][13] For the development of MLCCs, Ag-Pd was initially used as an internal electrode for its chemical stability. However, in recent years, Ni metal has been more commonly used for commercial reasons.…”
Section: Introductionmentioning
confidence: 99%